2010
DOI: 10.3329/jhpn.v28i1.4518
|View full text |Cite
|
Sign up to set email alerts
|

Drug-susceptibility Patterns of <i>Mycobacterium tuberculosis</i> in Mpumalanga Province, South Africa: Possible Guiding Design of Retreatment Regimen

Abstract: Multidrug-resistant tuberculosis (MDR-TB) has been a cause of concern in both developed and developing countries. The prevalence of drug resistance in Mycobacterium tuberculosis (MTB) isolates (n=692) from Mpumalanga province was assessed. In total, 692 (64%) MTB strains from cases with pulmonary TB were tested for susceptibility against rifampicin, isoniazid, ethambutol, and streptomycin using the MGIT 960 instrument. Two hundred and nine (30.2%) strains were resistant to one or more drugs. Resistance to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…Only one (0.53%) sample was susceptible to rifampicin. This is a first report of high drug resistant MTBC Port Elizabeth; these results are higher than those that were reported by Green et al [ 22 ] who reported on 58.4% MDR-TB in the Mpumalanga Province of South Africa.…”
Section: Resultscontrasting
confidence: 64%
“…Only one (0.53%) sample was susceptible to rifampicin. This is a first report of high drug resistant MTBC Port Elizabeth; these results are higher than those that were reported by Green et al [ 22 ] who reported on 58.4% MDR-TB in the Mpumalanga Province of South Africa.…”
Section: Resultscontrasting
confidence: 64%
“…Subba et al [ 17 ] also reported the mono-resistance among new cases to RMP and INH to be 0 and 13.33 % respectively. Green et al, reported 6.1 % resistance to RMP and 17.7 % resistance to INH from South Africa [ 26 ]. The resistance of Mycobacterium tuberculosis to RMP and INH is an alarming marker of MDR-TB [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the extensive use of streptomycin for the treatment of other bacterial infections. The use of standard anti-tubercular therapy in mono-DR-TB and poly-DR-TB posses a great risk of treatment failure leading to the development of MDR-TB in case of the mono-drug and poly-drugs (non-MDR) resistant cases [ 26 ]. The differences in the susceptibility patterns of M. tuberculosis in other countries and in Nepal, may be due to the difference in effectiveness of tuberculosis control program in different countries and difference in other risk factors like previous TB treatment, improper and/or incomplete treatment, smoking habit, poverty, illiteracy, migration to/from high MDR-TB prevalence areas, alcoholism, poor housing, overcrowding and homelessness in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent follow-up studies evaluating this regimen observed, even after cure, very high rates of recurrence in TB patients with MDR-TB at base-line [ 21 , 22 ]. Notwithstanding, most TB programmes in low-income countries in sub-Saharan Africa treat, empirically, every year 10-20% of their TB patients using this regimen [ 2 , 15 , 19 ]. The design of NTP retreatment regimens depends on the epidemiological context, the program's performance, and the means available.…”
Section: Discussionmentioning
confidence: 99%